Symposium 3: Where is the Learning in Networked Learning? Symposium Introduction - Hodgson, Vivien (Proceedings of the International Conference on Networked Learning, 2008)
In this symposium the intention is to bring together a collection of papers where we will revisit the early description of networked learning that researchers at particularly Lancaster but also Sheffield University have worked with since the nineties i.e. Networked learning is learning in which information and communications (ICT) is used to promote connections: between one learner and other learners, between learners and tutors; between a learning community and its learning resources (Goodyear, P. Banks, S. Hodgson, V. and McConnell, D.) Each of the papers will focus particularly on the learning aspect of networked learning and how, in both theory and practice, ideas about the design, experience and processes of learning are seen and have developed over the ten years since this description of networked learning was first written into a JISC research proposal in 1998. An emphasis of the symposium will be to explore, in more depth, the nature of the connections that are made within networked learning and the way these connections have come to be discussed and analysed from a learning perspective. In particular, the papers pick up on different aspects of ideas emerging from social practice and socio-cultural theories applied to conceptualisations of collaborative learning, which have come to be closely associated with networked learning. The symposium includes the following papers; Maria Zenios and Peter Goodyear; Where is the learning in networked knowledge construction? Chris Jones; Networked Learning - a social practice perspective Thomas Ryberg; The Metaphor of Patchworking as a Viable Concept in Developing Networked Learning? Gale Parchoma, and Mary E. Dykes; Bridging Networked learning between the Knowledge Economy and Higher Education: A philosophical Approach Debra Ferreday, D and Vivien Hodgson; The Tyranny of Participation and collaboration in Networked Learning